Visual Culture and the anthropological insight - DOI 10.5216/vis.v10i1.23083 - Campos, Ricardo (2013)
With this paper we intend to reflect on the possibilities of a closer relationship between the discipline of Anthropology and the interdisciplinary field of Visual Culture. If it is true that, although residual, the presence of the visual sphere has always been a crucial feature in the history of anthropology, it also seems clear that the connection between image and this scientific discipline has been essentially constructed on the basis of a practical use of the visual technologies (photography, cinema, video). Thus the importance granted to the visual methodologies in fieldwork and the consequent production of visual documents (ethnographic films, photoessays, etc.). Currently the field of Visual Culture, forged at the crossroads of multiple disciplinary interests and assets, suggests that the visual dimension in human culture is highly complex, making way to new approaches informed by different perspectives and theoretical and methodological frameworks. In this context, we believe that anthropology, with its prime methodological practice - ethnography – has something to say. It can contribute to thicken the debates around human visuality, regarding essentially the social processes of visual production, sharing and consumption.Keywords: Visual culture, visual anthropology, ethnography, visual methods